2020
DOI: 10.1016/s2214-109x(19)30447-4
|View full text |Cite|
|
Sign up to set email alerts
|

Affordability of the EAT–Lancet reference diet: a global analysis

Abstract: Background The EAT-Lancet Commission drew on all available nutritional and environmental evidence to construct the first global benchmark diet capable of sustaining health and protecting the planet, but it did not assess dietary affordability. We used food price and household income data to estimate affordability of EAT-Lancet benchmark diets, as a first step to guiding interventions to improve diets around the world. Methods We obtained retail prices from 2011 for 744 foods in 159 countries, collected under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
339
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(410 citation statements)
references
References 21 publications
13
339
2
3
Order By: Relevance
“…This could contribute to overcoming a major barrier identified by the stakeholders-the high price of protein-rich processed products. This barrier follows that of previous studies [47], who identified that healthier foods are likely unaffordable for low income populations. A shift to healthier diets may therefore require higher incomes, nutritional assistance and lower prices, representing considerable social and economic transformations.…”
Section: Discussionsupporting
confidence: 65%
“…This could contribute to overcoming a major barrier identified by the stakeholders-the high price of protein-rich processed products. This barrier follows that of previous studies [47], who identified that healthier foods are likely unaffordable for low income populations. A shift to healthier diets may therefore require higher incomes, nutritional assistance and lower prices, representing considerable social and economic transformations.…”
Section: Discussionsupporting
confidence: 65%
“…65 Additionally, Hirvonen et al also concluded that the PHD was affordable in high-income countries such as Australia, also consistent with the present study's ndings. 67 A 2013 global review on food prices and affordability showed that for some consumers price is more of a purchasing determinant than taste, and that consumers generally purchase more food when prices fall and less food when prices rise. 54 Although the affordability of the PHD for metropolitandwelling Australians shopping at major supermarkets has now been demonstrated, it remains unclear if, and to what extent, the cost of uctuating food prices could affect consumer adoption of this diet, particularly lower-income consumers who are more price sensitive than higher-income consumers.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Since the present study was completed, other research on the affordability of the PHD throughout the world has since been published, nding that the PHD was affordable for high-income countries such as Australia, but unaffordable for low-income countries. 67 The aims of this study were to: (a) Determine the affordability of the PHD food basket for low, middle and high socio-economic groups in metropolitan Australia; (b) Determine if the PHD food basket is more or less affordable than the Typical Australian Diet (TAD) food basket for low, middle and high socio-economic groups in metropolitan Australia.…”
Section: Is a Healthy And Sustainable Diet Affordable For Australians?mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the controversies regarding the affordability and effectiveness of the new ‘planetary diet’ (Hirvonen et al . 2019), the recent approach presented in the EAT‐Lancet report (Willett et al . 2019) has received much attention as a blueprint for feeding 10 billion people by 2050 while retaining planetary health.…”
Section: Introductionmentioning
confidence: 99%